Politeness in Javanese Krama Inggil: A Study of Daily Conversations in a Transmigration Community in South Sumatra - Siyam Safitri; Dessy Wardiah; Sri Wahyu Indrawati (Journal of Social Work and Science Education, 2026)
This study examines the realization of language politeness in daily conversations using Javanese Krama Inggil in Gunung Terang Village, Madang Suku I District, East OKU Regency, South Sumatra, Indonesia. Using a qualitative descriptive method, data were collected through observation, recording, and note-taking from 27 native Javanese speakers who actively use Krama Inggil in daily interactions. The analysis employed Geoffrey Leech's six politeness maxims: tact, generosity (acceptance), praise, humility, agreement, and sympathy. Of 27 utterances analyzed, 24 (88.9%) adhered to politeness principles, while 3 (11.1%) violated them. The maxim of praise was most frequently observed (6 utterances), followed by the maxim of tact (6 utterances), maxim of generosity (5 utterances), maxim of sympathy (3 utterances), maxim of agreement (2 utterances), and maxim of humility (2 utterances). Violations occurred in the maxims of generosity, praise, humility, and sympathy. The findings indicate that the Gunung Terang community maintains a relatively high level of politeness in Javanese Krama Inggil usage, though generational and social factors contribute to occasional violations. This study contributes to the documentation of Javanese politeness practices in transmigration communities outside Java, an under-researched context. The findings have implications for language preservation efforts and intercultural communication studies.